2007
DOI: 10.1590/s0100-736x2007001200007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de éguas repetidoras ou não de cio através da avaliação histológica do endométrio e das concentrações plasmáticas de progesterona

Abstract: Comparative study of repeat breeds and healthy mares through endometrial Comparative study of repeat breeds and healthy mares through endometrial Comparative study of repeat breeds and healthy mares through endometrial Comparative study of repeat breeds and healthy mares through endometrial Comparative study of repeat breeds and healthy mares through endometrial histology and plasmatic progesterone concentrations histology and plasmatic progesterone concentrations histology and plasmatic progesterone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Following, the material obtained was fixed in Bouin solution (75 % saturated picric acid solution, 25% formaldehyde and 5% glacial acetic acid) for a period of 24 hours (Eigenheer- Moreira et al 2007, Moraes et al 2007, Aleixo et al 2011. Then, the samples were dehydrated with increasing concentrations of ethanol, cleared in xylene and included in paraffin (Drummond et al 2004).…”
Section: Histological Preparationmentioning
confidence: 99%
“…Following, the material obtained was fixed in Bouin solution (75 % saturated picric acid solution, 25% formaldehyde and 5% glacial acetic acid) for a period of 24 hours (Eigenheer- Moreira et al 2007, Moraes et al 2007, Aleixo et al 2011. Then, the samples were dehydrated with increasing concentrations of ethanol, cleared in xylene and included in paraffin (Drummond et al 2004).…”
Section: Histological Preparationmentioning
confidence: 99%
“…Moreover, not all mares with more severe changes present reproductive failure (Silva et al, 1987). However, subfertility was directly related to the animal's age (Eigenheer-Moreira et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The only mare that had an endometrium close to normal was mare 6, in which no change of any kind was observed regarding inflammatory infiltrates and fibrosis, and was therefore classified into category I. A study by Eigenheer-Moreira et al (2007) concluded that the animals that presented the most severe endometritis and fibrosis as histological changes were those with more estrus repetitions. The presence of mild to moderate changes does not necessarily imply that the mare will not be able to carry a pregnancy to term.…”
Section: Discussionmentioning
confidence: 99%
“…In the hands of a reasonably experienced operator, this procedure has few complications and side effects (Van Camp, 1988), and there is no apparent negative effects on reproductive performance (Kenney, 1978). Endometrial biopsy is an established minor surgical procedure that is modestly invasive, easy and a cheap diagnostic technique, with the most common sequelae being slight bleeding at the biopsy site (Eigenheer‐Moreira et al, 2007; Sertich, 1996; Snider et al, 2011). This rapid technique is frequently included in the examination for breeding soundness evaluation and additionally is capable of estimating the mare's ability to carry a foal to term (Snider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%